2020
DOI: 10.1111/ppa.13269
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and phenotypic characterization of Phytophthora infestans populations on Java, Indonesia

Abstract: Populations of P. infestans are dynamic, with mutation, migration, sexual reproduction, and host having contributed to the evolution of new clonal lineages or genotypes with different epidemiological, genotypic, and phenotypic characteristics (Goodwin, 1997; Hu et al., 2012). Globalization has increased the trade in agricultural commodities such as potato between countries. Potato tubers intended for processing or for use as seed are imported or exported from one country to another based on supply and demand. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…This is also shown by a low genetic differentiation among these populations. High genotypic diversity through sexual reproduction and oospores’ formation is common in neighboring countries such as Finland and the Baltic region [ 26 , 32 , 68 ], but differs from essentially clonal populations in western regions of Europe [ 72 , 73 , 74 ], and in the United States and South America [ 75 , 76 ], Asia [ 61 , 77 ], and Africa [ 78 , 79 ]. However, recent rapid local and global genotype shifts have occurred due to pathogen migration with tuber trade [ 80 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is also shown by a low genetic differentiation among these populations. High genotypic diversity through sexual reproduction and oospores’ formation is common in neighboring countries such as Finland and the Baltic region [ 26 , 32 , 68 ], but differs from essentially clonal populations in western regions of Europe [ 72 , 73 , 74 ], and in the United States and South America [ 75 , 76 ], Asia [ 61 , 77 ], and Africa [ 78 , 79 ]. However, recent rapid local and global genotype shifts have occurred due to pathogen migration with tuber trade [ 80 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…infestans population in Indonesia has been very little studied until recently; Nishimura et al (1999) reported on four isolates (all A2) collected in 1993 and two of these were further characterized by Gotoh et al (2005) as JP‐1. However, during 2016–2019, Dangi et al (2021) collected 140 FTA card samples of P . infestans from the three main potato‐growing areas of the island of Java, where 50% of Indonesia's potatoes are produced.…”
Section: Country Profilesmentioning
confidence: 99%
“…It was reported that the application of mancozeb was no longer effective in controlling leaf blight disease in tomato crops (Syahputra, 2018). Dangi et al (2020) also stated an indication of reduction sensitivity of…”
Section: Introductionmentioning
confidence: 99%
“…isolated from Colombia in 2018 reached its maximum growth on a 9 cm petri dish within 7 to 10 days. Meanwhile, P. infestans isolated from several regions in Indonesia including Garut in 2019 took about 7 to 10 days to fully cover the surface of the culture medium in a 9 cm petri dish(Dangi et al, 2020).…”
mentioning
confidence: 99%